Fishing for the Future: How FishGov2 is Transforming Fisheries and Aquaculture in Africa - Lumba, Patricia Mweene; Mutegi, Angela (AU-IBAR, 2024)
This publication captures the powerful stories of impact emerging from FishGov2, showcasing ground-breaking milestones and game-changing innovations. From empowering women in fisheries with greater market access to unlocking new economic opportunities in aquaculture, these initiatives are revolutionizing the sector. The ripple effects are profound: improved governance, strengthened sustainability, and the widespread adoption of best practices that are shaping a more resilient future.
Keywords: Aquaculture Development; Fisheries Management; Empowering fisherwomen; Climate resilience; Blue Economy